Protection Of Victims' Rights In Cases Of Maltreatment That Resulted In Death: A Case Study Of Ronald Tannur - Wardhana, Adi Pratomo Kusuma; Santoso, Agnellya Hendarmin; Joseph Sinatra, Tristan Canari; Nurwantoko, Endro Try; Andryawan, Andryawan (Fakultas Hukum Dehasen, 2025)
This research aims to analyze how victims' rights are protected in Indonesia for cases that occur such as abuse and what laws can be imposed on the perpetrator through the case of Ronald Tannur who abused his girlfriend. The research method used in writing this paper is the normative legal research method (normative doctrinal-juridical). In this research, the author uses primary legal materials and secondary legal materials. In this research, the researcher used library materials as the main material for analyzing cases, and in conducting research. Normative legal research is a process of finding legal rules, legal principles and legal doctrines. The legal materials used in this research are primary legal materials and secondary legal materials. Primary legal materials include statutory regulations and official documents that contain legal provisions, while secondary legal materials are legal materials that provide explanations regarding primary legal materials. The results obtained in this research show that there are various legal bases that have been implemented in Indonesia, such as regulations that have been issued and stipulated by the government which regulate the protection of victims' rights, one of which is Undang-Undang (UU) Nomor 13 Tahun 2006 tentang Perlindungan Saksi dan Korban in Indonesia. Apart from that, there are articles from the Kitab Undang-Undang Hukum Pidana that can sentence such perpetrators to prison, such as Pasal 338 of the Kitab Undang-Undang Hukum Pidana.